METHODS AND TOOLS FOR DEVELOPING COMPUTER LEARNING SOFTWARE ON ELECTRICAL ENGINEERING BASED ON WIKI TECHNOLOGY - Roman V. Alekhin; Pavel A. Butyrin; Pavel R. Varshavskiy; Alexander P. Eremeev (Открытое образование (Москва), 2016)
This work is devoted to issues related to the development of learning software and, in particular, digital libraries and knowledge bases in different fields and disciplines. Main attention is paid to the development of computer learning software for electrical engineering on the base of rapidly growing and popular wiki technology. This work was supported by RFBR (projects 12-08-00358, 14-01-00427, 12-07-00508).